Highly Stretchable Starch Hydrogel Wearable Patch for Electrooculographic Signal Detection and Human–Machine Interaction. Issue 12 (5th November 2021) - Wan, Shu; Wu, Nan; Ye, Yizhou; Li, Shunbo; Huang, Haizhou; Chen, Li; Bi, Hengchang; Sun, Litao
Abstract : It is crucial to prepare wearable devices with high stretchability to reduce the mechanical mismatch when attached to the skin. Recently, pure polysaccharide‐based hydrogels have been intensively focused on due to the living matter‐like softness, abundance, inherent biocompatibility, complete biodegradability, and renewability. However, it remains a significant challenge to achieve pure polysaccharide‐based hydrogels with high stretchability. Herein, a facile strategy is presented to synthesize a highly stretchable hydrogel wearable patch by integrating the starch (from lotus rhizome) as skeleton and sodium chloride as the electrolyte, exhibiting several advantages such as low modulus (≈4.4 kPa), broad stretching range (0≈790%), high ionic conductivity (10 S m −1 ), high linearity (0.996, 0≈300%), and good reproducibility (>1000 cycles). Surprisingly, both stretchability and softness have surpassed those of other pure polysaccharide‐based hydrogels reported in the literature. Furthermore, the combination of the adhesion, the low modulus, and stretchability can realize conformal attachment to different kinds of uneven objects, including the skin. Based on these properties, an electrooculographic (EOG) signal acquisition system and a relevant prototype video game using starch hydrogel patches are designed, exhibiting great potential in EOG signals monitoring as well as human–machine interaction. Moreover, other functions such as biocompatibility and biodegradability are demonstrated. Abstract : A facial strategy is introduced to synthesize a highly stretchable hydrogel patch based on lotus rhizome starch and NaCl. This kind of hydrogel patch possesses several advantages, such as inherent biocompatibility and biodegradable. These characteristics together make the hydrogel attractive to transduce electrophysiological signals and in appliances with increased human–machine interaction.